Biogeographic Distribution Patterns of Bacteria in Typical Chinese Forest Soils - Xia, Zongwei; Bai, Edith; Wang, Qingkui; Gao, Decai; Zhou, Jidong; Jiang, Ping; Wu, Jiabing (Frontiers in Microbiology, 2016)
Microbes are widely distributed in soils and play a very important role in nutrient cycling and ecosystem services. To understand the biogeographic distribution of forest soil bacteria, we collected 115 soil samples in typical forest ecosystems across eastern China to investigate their bacterial community compositions using Illumina MiSeq high throughput sequencing based on 16S rRNA. We obtained 4,667,656 sequences totally and more than 70% of these sequences were classified into five dominant groups, i.e. Actinobacteria, Acidobacteria, Alphaproteobacteria, Verrucomicrobia and Planctomycetes (relative abundance > 5%). The bacterial diversity showed a parabola shape along latitude and the maximum diversity appeared at latitudes between 33.50°N and 40°N, an area characterized by warm-temperate zones and moderate temperature, neutral soil pH and high substrate availability (soil C and N) from dominant deciduous broad-leaved forests. Pairwise dissimilarity matrix in bacterial community composition showed that bacterial community structure had regional similarity and the latitude of 30°N could be used as the dividing line between southern and northern forest soils. Soil properties and climate conditions (MAT and MAP) greatly accounted for the differences in the soil bacterial structure. Among all soil parameters determined, soil pH predominantly affected the diversity and composition of the bacterial community, and soil pH = 5 probably could be used as a threshold below which soil bacterial diversity might decline and soil bacterial community structure might change significantly. Moreover, soil exchangeable cations, especially Ca2+ (ECa2+) and some other soil variables were also closely related to bacterial community structure. The selected environmental variables (21.11%) explained more of the bacterial community variation than geographic distance (15.88%), indicating that the edaphic properties and environmental factors played a more important role than geographic dispersal limitation in determining the bacterial community structure in Chinese forest soils.